A importância do ensino de libras para crianças surdas nos anos iniciais da educação básica - MORAES, Hillary Suzan Medeiros de (2022)
This article is important to approach, understand and reflect on the teaching of LIBRAS (Brazilian Sign Language) in early childhood education, seeking to answer the problematic question of: why is literacy in Libras not integrated into initial classes, even being prescribed as a second language in Brazil in addition to understanding how the teaching of Libras works in the early years of basic education. The main objective of this work is to emphasize the importance of inclusive education in the early years. The theoretical framework of this work begins with a brief historical perspective on inclusive education for people with deafness, then it addresses education for deaf students in basic education, that is, in the early years of basic education, addressing this communication between deaf students and listeners within the classroom. Finally, the theoretical framework of this work addresses educational policies for students with deafness in Brazil, in the early years of basic education. Through this research it was observed that it is of enormous importance that schools can include the teaching of LIBRAS in the early years, so that this language can perpetuate itself as common, promoting more and more an egalitarian and inclusive education for students with hearing impairment.